The economic efficiency of public safety zones around the airport - Государська, І.Л. (Proceedings of National Aviation University (archive), 2009)
Economic efficiency of creation of Public Safety Zones within airporthave been considered, that is based on cost-benefit analysis. Estimation of costs and the benefits have been presented from moving of private building, public buildings, road infrastructure or other structures or from change of land use within Public Safety Zones by cost of individual risk within the area interest. Advantage of the benefits from creation of Public Safety Zones within airport has been represented that are higher than costs.